Educational trends in Argentina: an analysis based on measurements of flows and levels of schooling, 1974-2009 - Rojas, Mara Leticia (2011)
In this paper they are proposed and analyzed measures of educational levels (by defining the variables "years of education" and "greater educational attainment") as well as educational flows (through the estimation of "gross" and "net enrollment rates") in order to observe their recent evolution and to make an updated profile of the distribution of educational attainment across the Argentinean population. Unlike most of the literature, the use of household survey allows the construction of educational indicators as levels and cycles actually finished without additional restrictive assumptions such as the average years of repetition or dropout. It will see that, although the flows evolution in terms of enrollment rates has been positive, there has been an enlargement of the gap between gross and net enrollment rate and they strongly depend on economic shocks. In addition, the stock measured by levels and years of education shows two points of concentration in the distribution across the population space. These observations open up questions about the quality and effectiveness of future educational stock and about the polarization existing today.